2013
DOI: 10.1371/journal.pone.0056387
|View full text |Cite|
|
Sign up to set email alerts
|

Calreticulin Induces Dilated Cardiomyopathy

Abstract: BackgroundCalreticulin, a Ca2+-buffering chaperone of the endoplasmic reticulum, is highly expressed in the embryonic heart and is essential for cardiac development. After birth, the calreticulin gene is sharply down regulated in the heart, and thus, adult hearts have negligible levels of calreticulin. In this study we tested the role of calreticulin in the adult heart.Methodology/Principal FindingsWe generated an inducible transgenic mouse in which calreticulin is targeted to the cardiac tissue using a Cre/lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 48 publications
1
45
0
Order By: Relevance
“…The CALR protein is localized primarily in the endoplasmic reticulum through its C-terminal KDEL motif [3], but it is also found in the cell membrane, cytoplasm, and extracellular matrix [4,5]. Functionally, CALR is believed to participate in Ca2+ homeostasis as a calcium-binding protein, handling misfolded proteins, cell adhesion, immune response to cancer, and phagocytosis [4,6,7,8,9,10,11,12,13]. CALR-knockout mice are born dead and display impaired cardiac development, whereas postnatal overexpression also leads to cardiac defects [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The CALR protein is localized primarily in the endoplasmic reticulum through its C-terminal KDEL motif [3], but it is also found in the cell membrane, cytoplasm, and extracellular matrix [4,5]. Functionally, CALR is believed to participate in Ca2+ homeostasis as a calcium-binding protein, handling misfolded proteins, cell adhesion, immune response to cancer, and phagocytosis [4,6,7,8,9,10,11,12,13]. CALR-knockout mice are born dead and display impaired cardiac development, whereas postnatal overexpression also leads to cardiac defects [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, cardiac-specific CRT overexpression could induce DCM characterized by impaired left ventricular systolic and diastolic function, complete heart block, and sudden death in mice [19,20]. Recently, we reported that CRT was significantly upregulated in the myocardium of a rat model of furazolidone-induced DCM, resulting in apparent mitochondrial dysfunction via CRT-STAT3 (signal transducer and activator of transcription 3) signaling pathway [11].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies revealed that forced induction of apoptosis in the mouse heart leads to DCM [10,11]. Accordingly, a caspase-8 transgenic mouse model that develops heart failure can be rescued by inhibition of apoptosis [10].…”
Section: Introductionmentioning
confidence: 99%